(untitled) (PIONIR: JURNAL PENDIDIKAN, 2022)
This study aims to reveal (1) the effect of motivation on teacher performance (2) the effect of job satisfaction on teacher performance. This research was conducted at a public elementary school in Banda Aceh City. The study population was all teachers of public elementary schools in the city of Banda Aceh totaling 481 people. Determination of the sample using the Slovin formula, with a total sample of 218 people. Data were collected using a questionnaire filled out by respondents from teachers. The research analysis used descriptive analysis and inferential analysis with Path Analysis. The results showed that: 1) work motivation had a significant and significant effect on teacher performance and 2) job satisfaction had a significant and significant effect on teacher performance. The teacher performance model, the findings of this study explain that improving teacher performance can be done through work motivation and job satisfaction which will directly lead to better teacher performance.